2019
DOI: 10.1016/j.chb.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Recognition in makerspaces: Supporting opportunities for women to “make” a STEM career

Abstract: Making is a playful exploration of tools and materials to design personally meaningful artifacts, providing a particularly impactful entry point for traditionally underrepresented youth in science, technology, engineering, and mathematics (STEM) fields. However, it remains unclear how these constructionist explorations translate to eventual professional and educational STEM opportunities, especially for women. This paper tracks an exemplary case in a makerspace to theorize, describe, and analyze the behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…Many international studies highlighted the overlapping between new pedagogies and the educational makerspace culture (Lahmar et al, 2017) and in their review of the literature, Vossoughi and Bevan (2014) showed how the makerspace culture of peer support and scaffolding aligns with Lev Vygotsky’s (1978) theory, the interest-driven activities from a makerspace reminding of the learner-driven approach and inquiry-oriented pedagogies and of Freire’s (2005) critical educational theory. But arguably, the most influential pedagogy was the constructionism (Papert, 1993), regarded as the foundational theory of the maker movement in education (Keune et al, 2019; Marsh et al, 2017; Martinez and Stager, 2013; Tan, 2019). Advocating for the use of technology in school not as an add-on for the instructional process, but as ‘object-to-think-with’ for children’s development (Papert, 1980), Papert considers that learning happens best when one concretely makes and publicly shares or displays objects.…”
Section: Makerspaces For Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Many international studies highlighted the overlapping between new pedagogies and the educational makerspace culture (Lahmar et al, 2017) and in their review of the literature, Vossoughi and Bevan (2014) showed how the makerspace culture of peer support and scaffolding aligns with Lev Vygotsky’s (1978) theory, the interest-driven activities from a makerspace reminding of the learner-driven approach and inquiry-oriented pedagogies and of Freire’s (2005) critical educational theory. But arguably, the most influential pedagogy was the constructionism (Papert, 1993), regarded as the foundational theory of the maker movement in education (Keune et al, 2019; Marsh et al, 2017; Martinez and Stager, 2013; Tan, 2019). Advocating for the use of technology in school not as an add-on for the instructional process, but as ‘object-to-think-with’ for children’s development (Papert, 1980), Papert considers that learning happens best when one concretely makes and publicly shares or displays objects.…”
Section: Makerspaces For Childrenmentioning
confidence: 99%
“…Apart from the alignment of new pedagogies with the pedagogical approach from makerspaces, another reason for which they are so appealing to the education system is the recent emphasis across the world on science, technology, engineering and mathematics (STEM) education and digital literacies and the promise makerspaces make in this regard (Barton et al, 2017; Keune et al, 2019; Marsh et al, 2017). As much need for STEM education as there is (Kelley and Knowles, 2016), this sole identification of makerspaces with STEM and digital technologies could create some problems with their implementation and the attracted audience.…”
Section: Makerspace In Education and Its Promise For Stem Learningmentioning
confidence: 99%
See 1 more Smart Citation
“… Researchers in the learning sciences have an ongoing interest in how makerspaces can encourage girls and women to pursue STEM related fields (see Keune, Peppler & Wohlwend, 2019). …”
mentioning
confidence: 99%
“…The purpose of this study is to know what women who have been students at our school as well as those currently enrolled have to say in order to improve the overall experience for new students and to increase the number of female students enrolled at our school. As in many other countries, the number of women in higher education and in our case, in STEM, can be an indicator of equal opportunities for women [2][3][4]. This work is the beginning of a project to improve the overall experience of our female students and to improve our attraction of talent processes so that more girls choose to study Engineering and Science in the most impoverished region of Mexico.…”
Section: Introductionmentioning
confidence: 87%